Characterizing proximal risk for depressive symptoms and suicidal ideation with acute cannabis use and withdrawal among adolescents using ecological momentary assessment: Study protocol - Isabella Feibus; Marta Borrego Mahiques; Meghan Costello; Kevin Potter; Kate H. Bentley; Bettina B. Hoeppner; Luwei Liu; Bryn Evohr; Lynn Yan; Jodi Gilman; A. Eden Evins; Joe Kossowsky; et al. (PLoS ONE, 2025)
Background Heavy cannabis use often co-occurs with symptoms of depression in adolescents. Adolescents with past-year cannabis use are at increased risk of major depressive episodes and cannabis use is more than twice as common in adolescents with depression compared to those without. This study seeks to disentangle relationships between acute cannabis use, withdrawal, and abstinence on proximal depression and suicide risk using ecological momentary assessment (EMA) within the context of a randomized controlled trial comparing the effects of cannabis abstinence to cannabis use as usual. Methods This study will enroll 200 adolescents aged 12–18 who have daily or near-daily cannabis use and current depressive symptoms. Participants will complete 12 study visits over a 10-week period. At visit 2, participants will be randomized (1:1) to either 8 weeks of sustained cannabis abstinence encouraged through contingency management (CB-Abst) or a monitoring control group (CB-Mon). All participants will complete self-report and interview-based measures of substance use and symptom severity, along with 3 phases of EMA data collection (4 total weeks), involving 8 daily surveys that inquire about past-hour substance use, mood, and situational context. Phases will take place during baseline cannabis use, immediately after randomized abstinence, and following 8 weeks of sustained abstinence. The primary outcomes will be EMA-measured depressive symptoms and suicidal ideation across the 3 EMA phases, by randomized group. Exploratory outcomes will include Fitbit-derived measures of sleep, circadian rhythms, and step count. Discussion This is the first study, to our knowledge, to evaluate the acute effects of cannabis use, withdrawal, and sustained abstinence on mood among adolescents with heavy cannabis use and co-morbid symptoms of depression. Results will characterize periods of risk for fluctuations in mood and suicidal ideation across the withdrawal period and aim to guide intervention development to reduce depression and suicide risk among adolescents. Trial registration ClinicalTrials.gov NCT06576076